Determinan Kemiskinan Multidimensional 34 Provinsi di Indonesia Periode Tahun 2015-2018 - Amartya Intan; Asih Murwiati; I Wayan (Journal on Education, 2023)
Poverty is faced by almost all countries in the world. Poverty is the inability of a person to meet basic needs. In calculating the SDGs poverty is placed in a multidimensional framework, namely looking at poverty from various dimensions and looking at the causes of poverty from various sides, which is set forth in SDGs 1 "No Poverty" with the vision of eliminating poverty in all its forms everywhere. The SDGs aim to eliminate poverty in all its forms wherever growth is slow, especially in the Southeast Asia region. Indonesia is ranked 5th in Southeast Asia with an achievement score of 69.16%, the calculation of poverty in Indonesia is not in line with SDGs 1 goals because it only emphasizes the monetary dimension. This study used data from 34 provinces in Indonesia for the 2015-2018 period to see the determinants of multidimensional poverty in Indonesia. This study shows that 1) The level of completion of high school education has a significant positive effect on multidimensional poverty in Indonesia, 2) Early marriage has no significant effect on multidimensional poverty in Indonesia, 3) Slums have a significant positive effect on multidimensional poverty in Indonesia.